Exploring the views of Muslim community on presumed consent system: A study conducted in Malaysia - Makmor Tumin; Khaled Tafran; NurulHuda Mohd Satar; Nawi Abdullah; Wan Ahmad Hafiz Wan Md Adnan; Mohd Yakub @ Zulkifli Mohd Yusoff (Indian Journal of Transplantation, 2016)
Background: Currently, Malaysia follows the informed consent (IC) system of organ donation; however, the rate of organ donation in the country appears very low, and implementing a presumed consent (PC) system could help in enhancing the rate of donation. In determining the success of PC system, exploring the Muslim's perception toward the system is crucial. Method: We conducted a questionnaire-based survey between October and December 2013. Self-administrated questionnaires were distributed among 829 Muslims in Kuala Lumpur. Results: The results show that 42.8% people of the Muslim community are unwilling to donate, while 17% of them are willing to sign objection form if the PC system were implemented. The PC system may violate the autonomy of about 25.8% of the Muslim community. Conclusion: Implementing the PC system would have helped Malaysia to overcome the issue of organ shortage considering the fact that the majority of the people from Muslim community are willing donors. However, it is also important to consider the unwilling donors' autonomy while designing the PC legislation, and further studies require understanding the reasons behind their reluctance to donate. We propose that a priority scheme for organ allocation should be included in organ donation legislation.